Evaluation of the cytotoxic activity of chemically characterized propolis originating from different geographic regions and vitamin D co-supplementation against human ovarian cancer cells - Eman Ali; Maged W. Helmy; Eman H. Radwan; Karoline K. Abdul Aziz; Aida A. Abd El-Wahed; Lamia M. El-Samad; Abeer El Wakil (BMC, 2024)
Abstract Ovarian cancer is the second most common and lethal gynecologic malignancy. Among natural product-based therapy, the honeybee products, particularly propolis, serve a valuable source contributing directly to human nutrition and health. In the present study, we determined the chemical composition of different types of propolis originating from Egypt, Germany and France using liquid chromatography-tandem mass spectrometry. The compounds identified belong to different metabolite classes, including flavonoids, cinnamic acid, chalcones, terpenoids, phenolic lipids, stilbenes, phenolic compounds, carbohydrates, vitamins, coumarins, polyprenylated benzophenone, benzoic acids, fatty acid methyl ester, and coumaric acid, and their derivatives. The most active extract is from France then Egypt and Germany. Afterwards, we treated the human ovarian cancer cells, OVCAR4, with different concentrations (1-400 μg/mL) of variable propolis types supplemented or not with vitamin D (0.0015-0.15 μg/mL) in order to evaluate the efficacy and the cytotoxic activities of our local P as compared to other types collected from different geographic regions. Importantly, the combinatorial treatment of OVCAR4 cancer cells with propolis and vitamin D in the same concentration ranges resulted in enhanced cell viability inhibition. Furthermore, such co-supplementation with vitamin D inhibits predominately the proliferative activity of cell population with the French propolis type as manifested by Ki67 expression, while it reduces considerably its expression, particularly with the German type, followed by the Egyptian one. Nowadays, scientists are interested by natural products which have risen to the forefront of drug discovery. Chemically characterized propolis showing cell viability inhibition and antiproliferative potential seems a valuable extract for further consideration as anti-carcinogenic agent. Graphical abstract